HISTORY OF THE FORMATION OF TRAVEL JOURNALISM (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article talks about the emergence of the concept of travel journalism and its formation and development as a profession. This direction of journalism, formed in foreign countries, is also reflected in the mass media of Karakalpakstan. The article contains controversial discussions about the concept of travel journalism.